2021
DOI: 10.3390/ijerph18020704
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Risk Factors and Health: An Umbrella Review of Meta-Analyses

Abstract: Background: Environmental health is a growing area of knowledge, continually increasing and updating the body of evidence linking the environment to human health. Aim: This study summarizes the epidemiological evidence on environmental risk factors from meta-analyses through an umbrella review. Methods: An umbrella review was conducted on meta-analyses of cohort, case-control, case-crossover, and time-series studies that evaluated the associations between environmental risk factors and health outcomes defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 112 publications
(81 reference statements)
0
31
1
1
Order By: Relevance
“…Our study aimed to investigate a possible cross-sectional association between exposure to urban noise and the prevalence of type 2 diabetes mellitus, obesity and hypertension in the city of Lisbon. We found no association between the considered factors, unlike other studies where authors found an increased risk of cardiometabolic diseases in populations exposed to noise [19][20][21][22][23][24][25][26].…”
Section: Discussioncontrasting
confidence: 99%
“…Our study aimed to investigate a possible cross-sectional association between exposure to urban noise and the prevalence of type 2 diabetes mellitus, obesity and hypertension in the city of Lisbon. We found no association between the considered factors, unlike other studies where authors found an increased risk of cardiometabolic diseases in populations exposed to noise [19][20][21][22][23][24][25][26].…”
Section: Discussioncontrasting
confidence: 99%
“… 26 Second, greenspace can mitigate environmental hazards, such as air pollution, noise, and air temperature, 5 which are well-documented environmental risk factors for a range of health outcomes. 57 , 58 , 59 Dzhambov and colleagues 60 carried out a scoping review of studies testing pathways linking greenspace to health and found that 43 studies explored the mediating role of air pollution, 11 explored the mediating role of noise, and 5 explored the mediating role of heat. Significant mediating effects were found in about half of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a slow poisoning by Cd or As exposure may lead to overall increases in mortality and a range of diseases (Clemens and Ma, 2016). Ingestion is one of the major routes for human exposure to hazardous minerals, while the food chain represents the primary source (Rojas-Rueda et al, 2021); therefore, we need to reduce the accumulation of the toxic minerals in the edible organs of plants.…”
Section: Introductionmentioning
confidence: 99%